2006
DOI: 10.1021/jp064676d
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation Study of the Structural Characteristics of Water Molecules Confined in Functionalized Carbon Nanotubes

Abstract: Molecular dynamics (MD) simulations were performed to study the structural properties of water molecules confined in functionalized carbon nanotubes (CNTs). Four CNTs, two armchair-type (6, 6), (7, 7) and two zigzag-type (10, 0), (12, 0) CNTs, representing different helicities and different diameters, were chosen and functionalized at their open ends by the hydrophilic -COOH and the hydrophobic -CH 3 groups. The structural properties of water molecules inside the functionalized CNTs, including the orientation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…Although a few theoretical works on TiO 2 are related to water [15][16][17][18], few have been focused on the diffusion of water confined in TiO 2 slits. Our previous works of molecular dynamics (MD) showed that the chemical modification of carbon nanotubes would affect the water behaviors [19][20][21][22][23]. It means that the chemical property of the solid surface plays an important role in the structural behaviors of confined water, and will accordingly influence their diffusion behavior.…”
mentioning
confidence: 99%
“…Although a few theoretical works on TiO 2 are related to water [15][16][17][18], few have been focused on the diffusion of water confined in TiO 2 slits. Our previous works of molecular dynamics (MD) showed that the chemical modification of carbon nanotubes would affect the water behaviors [19][20][21][22][23]. It means that the chemical property of the solid surface plays an important role in the structural behaviors of confined water, and will accordingly influence their diffusion behavior.…”
mentioning
confidence: 99%
“…A key step for this novel nanomedicine technology consists in delivering small amounts of aqueous solutions through the hollow interior of CNTs. When water is confined within small nanotubes, however, its properties, structure and dynamics change dramatically and differ considerably from those of bulk (see for instance [3,4,5,6,7]). The goal of this work is to use molecular dynamics for gaining further insights into some of the properties of water confined in CNTs.…”
mentioning
confidence: 99%
“…Cambre´et al [11] also observed the confined water CNTs directly by using Raman spectra and experimentally demonstrated the phenomenon of single-file transport of water into CNTs, which was firstly reported by Hummer et al [12]. Huang et al [13] used MD simulations to study the structural properties of water molecules confined in functionalized CNTs and found that the -CH 3 functional groups exert little special effects on the structural properties of water molecules while the configurations of -COOH groups, incurvature or excurvature, determine whether water molecules can enter the CNTs. both CF 4 plasma treating and fluorosilane grafting methods are performed to functionalize the CNTs.…”
Section: Introductionmentioning
confidence: 78%